METODE PERBAIKAN TANAH DENGAN JUTE FIBRE DRAIN - I Gusti Ngurah Nyoman Wismantara; I Komang Agus Ariana (Jurnal Ilmiah Telsinas, 2019)
Settlement problems can arise in construction of across in soft soil, especially the consolidation problems to need long time, whereas the concretion time to need short time relative. One way of overcoming these problems is the installation of Vertical Jute Fibre Drain in soft soil, it is the mean in order that to be able these drains speed up the consolidation process in the sub soft soil layers. The purpose of this method is to reduce the time required by the pore water to escape from the soil which also get to abbreviate for to reach the consolidation degree 90%, so that the damage of structure and maintenance cost can be reduced.